THE INFLUENCE OF PROFITABILITY, LEVERAGE, AND CORPORATE GOVERNANCE ON SUSTAINABILITY REPORT DISCLOSURE: EVIDENCE FROM ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Dina Aprilia; Kartika; Indah Purnamawati (JAT : Journal Of Accounting and Tax, 2025)
The purpose of this research is to examine whether profitability, leverage, and corporate governance have an effect on sustainability report disclosure in energy sector companies listed on the Indonesia Stock Exchange. This research used a quantitative method by utilizing sustainability report data and annual reports sourced from company websites and the IDX website. The population used in this research was 74 companies. Sampling used a purposive sampling technique. There were 34 companies that could be used as research samples with 68 observation data. The data analysis method used was multiple linear regression analysis. The results of the research indicate that profitability has no effect on sustainability report disclosure, leverage has a positive effect on sustainability report disclosure, and independent commissioners have no effect on sustainability report disclosure in energy sector.